Formulation of Business Strategy And It’s Implications On Marketing Strategy At Dynasty Resort Post Pandemic - Srianggareni, Ni Made; Kartika, Yulia Elsa; Sunu, Gede Gangga Wiweka; Paramananda, Komang Agus Sathya; Giantari, I Gusti Ayu Ketut; Widagda, I Gusti Ngurah Jaya Agung (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Tourism activities in the hospitality sector are paralyzed by the Covid-19 pandemic. This phenomenon resulted in a decrease in profits that impacted Menjangan Dynasty Resort. So, a marketing strategy is needed to increase profits sustainably. This research was conducted to identify internal and external variables, determine business position with IFAS-EFAS matrix and marketing strategy implications. Data were collected through interviews with eight managers and direct observation of the object of research. The data analysis technique used SWOT analysis and IFAS-EFAS matrix. The results of this study show that internal variables are identified based on strengths and weaknesses, and external variables based on opportunities and threats that largely affect the sustainability of the company. The current business position in quadrant V (Hold & Maintain) and the future in quadrant II (Grow & Build) are both at a moderate level. The implication on marketing strategy leads to the activation of relationship marketing.